Creation Rest: Exodus 20:8-11 and the First Creation Account - Haynes, Matthew; Kruger, P. Paul (Old Testament Essays, 2018)
The focus of this article is the Sabbath commandment as it is expressed in Exodus 20. A number of factors that contribute to its expression are examined: the place of the Decalogue in the life of Israel, the stipulations for proper Sabbath observance, and the reasoning and motivation that lie behind its keeping. Additionally, various facets of human life that mark the seventh day of creation are connected to specific terminology within the fourth commandment. The article concludes by arguing that the Sabbath commandment in Exodus, properly observed, is a picture of the seventh day of creation and that a desire to recover that situation motivates its keeping.